Implementation of Probationary Penalty Against Soldiers of the Indonesian National Army Who Are Proven to Have Committed the Crime of Insubordination with Real Actions - Achmad Adharis Wijaya; Potler Gultom; Sujono Sujono (JURNAL HUKUM SEHASEN, 2023)
Insubordination is a purely military crime where the perpetrator is a military person. The purpose of the crime of insubordination is that a subordinate with real actions threatens with violence aimed at his superior or his Commander. How is the regulation of insubordination criminal offense with real action in Indonesian military criminal law? How is the criminal liability of TNI members as perpetrators of the crime of insubordination with real actions based on the decision of Military Court III-19 Jayapura number 236-K/PM.III-19/AD/XI/2021. Regulation of the Crime of Insubordination by Actual Action in Indonesian Military Criminal Law. In cases of insubordination, Military Courts and General Courts differ in the stages of resolution and the rules used tend to be different even though they both regulate insubordination. In the Criminal Code, insubordination is regulated in Articles 459-461, while the specific regulation is regulated in Articles 106-109 of the KUHPM. the decision given by the judge is relatively light, because if you refer to the provisions governing the crime of insubordination, namely in the Military Criminal Code (KUHPM) insubordination is classified into the category of serious crimes because the penalty is above 5 (five) years in prison. This research uses the Normative Juridical research method with secondary data consisting of primary, secondary and tertiary legal materials. The regulation of the Crime of Insubordination with Real Actions in Indonesian Military Criminal Law should be regulated by KUHPM because the Crime of Insubordination is a special crime so that the regulation must also be made special. Criminal Liability of TNI Members as Perpetrators of Criminal Acts of Insubordination by Real Judges in deciding cases of Criminal Acts of Insubordination should provide heavy verdicts in accordance with the Articles contained in the KUHPM in order to create loyalty to superiors by adhering to the joints that have been contained in the Sapta Marga and the oath of the soldier.